EFFECTIVE HR MANAGEMEN STRATEGY TO IMPROVE COMPANY PERFORMANCE - Dendy Tirtoadisuryo; Frandy Putra Perdamen Tarigan; Akhmad Multazim; Stevianus Arief (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2025)
This study explores the impact of effective Human Resource (HR) management strategies on improving company performance. With organizations increasingly recognizing the role of HR in driving business success, the research examines various HR practices, including recruitment, training and development, performance management, employee engagement, and diversity and inclusion. Using a mixed- methods approach, the study combines quantitative surveys with HR professionals and employees to gather data on key performance indicators such as productivity, turnover rates, and job satisfaction. In addition, qualitative interviews with HR leaders and focus groups with employees provide deeper insights into the challenges, benefits, and best practices associated with these strategies. The findings indicate that organizations that adopt data-driven recruitment, invest in continuous employee development, and implement transparent performance management systems experience higher productivity, reduced turnover, and enhanced employee engagement. Furthermore, a strong focus on diversity and inclusion is shown to foster innovation and creativity, leading to improved business outcomes. The study concludes that strategic HR management plays a critical role in shaping organizational success and highlights the importance of adapting HR practices to meet evolving business needs. By aligning HR strategies with company goals, businesses can create a motivated, skilled, and committed workforce, driving sustainable growth and competitive advantage.